2008
DOI: 10.1002/cncr.23560
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group AT‐hook 1 (HMGA1) is an independent prognostic factor and novel therapeutic target in pancreatic adenocarcinoma

Abstract: BACKGROUND. High mobility group AT‐hook 1 (HMGA1) proteins are architectural transcription factors that are overexpressed by pancreatic adenocarcinomas. The authors hypothesized that tumor HMGA1 status represents a novel prognostic marker in pancreatic adenocarcinoma. They also tested the hypothesis that HMGA1 promotes anchorage‐independent cellular proliferation and in vivo tumorigenicity. METHODS. Tumor HMGA1 expression was examined by immunohistochemical analysis of tissues from 89 consecutive patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 24 publications
4
49
0
Order By: Relevance
“…Regarding clinical outcomes, high levels of HMGA1 mRNA/protein in the cancers were associated with shorter survival in patients with pancreatic ductal adenocarcinoma [24] and periampullary cancer but not those with pancreatic head cancer [47]. Liau et al [30] demonstrated that HMGA1 expression was an independent predictor of poor postoperative survival in patients with pancreatic adenocarcinoma. In addition, patients with lung cancer [43] and hepatocellular carcinoma [7] also showed the association with worse prognosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Regarding clinical outcomes, high levels of HMGA1 mRNA/protein in the cancers were associated with shorter survival in patients with pancreatic ductal adenocarcinoma [24] and periampullary cancer but not those with pancreatic head cancer [47]. Liau et al [30] demonstrated that HMGA1 expression was an independent predictor of poor postoperative survival in patients with pancreatic adenocarcinoma. In addition, patients with lung cancer [43] and hepatocellular carcinoma [7] also showed the association with worse prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…Overexpression of HMGA1 is a common phenomenon in many cancer types [1,2,5,7,9,10,17,24,30,43,47]. Roles of HMGA1 in carcinogenesis were implicated because HMGA1 overexpression induced tumor formation and metastasis in human breast epithelial cells in nude mice and transformation of Rat-1 fibroblast and CB33 human lymphoblastoid cells [40,50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 68 of the 81 studies, IHC was carried out on individual whole-slide tissue sections. In the remaining 15 studies, TMAs were created by using 2-mm (44, 85, 100, 103), 1.5-mm (46,48,84), 1.0-mm (74), or 0.6-mm (61,64,69,75,83) diameter cores from representative tissue regions; one study provided no core size details (116). For 2 studies, only automated scoring techniques were used (42,48).…”
Section: Included Studiesmentioning
confidence: 99%
“…These PSN-1 cells pretreated with HMGA1 antisense oligodeoxynucleotides failed to form xenograft tumors in nude mice (33). Liau et al showed that down-regulation of HMGA1 in pancreatic cancer cells by stably transfected shRNA vectors reduced proliferation in vitro and tumor growth in vivo (49). They hypothesized that tumor HMGA1 status represents an independent prognostic marker and HMGA1 proteins are therapeutic targets in pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%